2018
DOI: 10.1038/s41388-018-0615-3
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribosyl)ation of OVOL2 regulates aneuploidy and cell death in cancer cells

Abstract: Poly(ADP‐ribosyl)ation (PARylation) is a post‐translational modification by which poly ADP‐ribose (PAR) polymers are covalently added to proteins through a PAR polymerase (PARP). Here, we identify that the transcriptional regulator, OVOL2, is a novel substrate for PARP1 and can be PARylated at residues Lysine 145, Lysine 176, and Lysine 212, within the C2H2 zinc‐fingers domain. PARylated OVOL2 acts as a transcriptional suppressor directly inhibiting downstream expression of the E3 ligase, Skp2, which promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This evidence underscored a previously unknown function of OVOL2 in cancer. Indeed, some works reported an association of OVOL2 with inhibition of cancer cells' proliferation, but no mechanistic details or functional validation have been provided so far [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This evidence underscored a previously unknown function of OVOL2 in cancer. Indeed, some works reported an association of OVOL2 with inhibition of cancer cells' proliferation, but no mechanistic details or functional validation have been provided so far [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 PARP1-induced PARylation was a key event in OVOL2-mediated regulation of chromosome integrity and inhibition of cancer cell growth. 27 OVOL2 expression was associated with MET in OS cells and inhibited ZEB1 expression and OS progression. 12 OVOL2 played a key role in inhibiting NPC metastasis and maintaining the epithelial phenotype.…”
mentioning
confidence: 92%
“…OVO-like zinc finger 2 (OVOL2), a member of the OVO family of conserved zinc-finger transcription factors, can regulate embryonic development and cancer metastasis. [11][12][13][14][15][16][17] It has been reported that Ovol2 gene knockout (KO) in mice results in embryonic lethality before embryonic day 10.5, indicating that OVOL2 is involved in early embryonic development. [11] OVOL2 expression was shown to be downregulated in hepatocellular carcinoma and colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%